Algal community response to anthropogenic pollution and environmental change at Lake Baikal, Siberia, over recent centuries - Roberts, Sarah (2017)
Despite its large volume, Lake Baikal has been experiencing recent changes within its limnological and biological structure, as well as changes within lake water nutrient and dissolved organic carbon concentrations. The biological changes within Lake Baikal include alterations within the distribution and abundance of major phytoplankton and zooplankton groups. These limnological changes are likely to be from both climate warming and anthropogenic impact, particularly over the last few decades. Recent shoreline observations in the South and North regions of Lake Baikal have found large blooms of filamentous green algae, which has been associated with nutrient enrichment from surrounding settlements and growing tourism. This highlights the question as to whether the pelagic regions are similarly showing any signs of anthropogenic driven nutrient enrichment. The aim of this thesis was to examine if pelagic Lake Baikal is showing any evidence of eutrophication and/or response to climate warming. The main themes of the research were to assess the modern-day limnological condition of Lake Baikal in the summer (August 2013) and winter (March 2013) months,and to examine Baikal’s phytoplankton response to nutrient enrichment via the construction of mesocosm experiments. High-resolution limnological change was then reconstructed from sediment cores across the lake. Sites were chosen within pelagic regions, bays and shallow waters nearby river inflows, and palaeolimnological records were used to assess primary production changes and floristic changes over the last few centuries. This timespan enables both natural variability within the system to be explored, and more recent changes pre and post known human influence within the catchment area (c. 1950 AD). The main palaeolimnological techniques applied for primary production proxies were sedimentary algal pigments, stable isotope analysis of bulk organic carbon and diatom valve concentrations. Mercury analyses was also applied to water samples and sediment cores as a pilot study to explore toxic metal pollution at Lake Baikal, due to mining activity along the Selenga River, and examine historic levels of mercury contamination, and examine historic levels of mercury contamination. Both modern-day limnological surveys and palaeolimnological records seem to be showing increasing algal biomass (chlorophyll-aconcentrations) over the last 60 years, with decreasing trends in diatom production (from diatoxanthin pigment concentrations and diatom valve concentrations) in the South basin. Spatial survey data represents a snap shot in Baikal’s limnology in late summer (August 2013), and shows higher than expected concentrations of total phosphorus within the mixing layer, which fall within the meso-eutrophic range. Dissolved organic carbon concentrations seem to now be higher within Lake Baikal’s waters, and both nitrate and silicate concentrations appear to be similar to known previous concentrations at Lake Baikal. A pilot study of mercury concentrations within Lake Baikal waters and sediments, show no signs of mercury contamination from mining activity along the major river inflows, and atmospheric deposition. Experimental results show that within the pelagic regions of Lake Baikal, nitrogen, phosphorus and silicon are influencing algal communities, with Si addition stimulating diatom growth, nitrogen and phosphorus addition stimulating chlorophyte growth, although overall nutrient treatments did not increase chlorophyll-a yield.Interestingly, experimental findings also highlight the potential influence of picocyanobacteria populations on silicon cycling. Concentrations of sedimentary chlorophyll-a concentrations (plus its derivatives) rise prior to major industrial influence within the Baikal catchment region, and stable carbon isotope records show a positive correlation with chlorophyll-a concentrations in the South basin, Selenga and Maloe More sites. Total phosphorus concentrations could be a result of both anthropogenic nutrient pollution, entering into the lake via the Selenga River, and climate driven changes in lake stratification and nutrient utilisation by algae. Results from limnological surveys and palaeolimnological records are thus likely to be reflecting both recent anthropogenic impact and climate change (rising lake water temperatures, declining ice cover thickness and duration and increasing river inflow from permafrost thaw), within the pelagic regions, especially given that recent work provides evidence of toxic cyanobacterial and chlorophyte blooms within the shallow waters of Lake Baikal. For the Maloe Moresite, which is a bay of the Central basin, results show a rise in sedimentary chlorophyte pigments post 1950 AD, suggesting that this bay region of Lake Baikal is currently being affected more than deeper water sites, by human influence, showing signs of eutrophication due to a switch in algal community composition.